(untitled) (Journal of the College of Education for Women, 2019)
The study aims to identify the Traumatic Symptoms (physiological, emotional, and cognitive) of earthquakes among the targeted sample; it also aims to identify the significant differences between psychological, emotional, and cognitive traumatic symptoms of earthquakes according to the gender and age of participants. The study additionally seeks to identify thepsychological positive-negative reactions associated with earthquakes according to gender and age of the participants. To measure the traumatic symptoms of earthquakes, a 4-point Likert scale questionnaire with (20) items (questions) accompanied with a 4-point Likert scale questionnaire with (18) items (questions) were used to measure the Psychological positive-negative reactions were administered to a sample of (230) participants. The results revealed that the sample did not show the traumatic symptoms during and after the earthquake, there are significant differences between the psychological, emotional, and cognitive traumatic symptoms in favor of females. There is a significant correlation relationship between the symptoms of traumatic (Psychological, emotional, and cognitive) of earthquakes and age which means the more the age of the participant, the less of the traumatic symptoms and vice versa. The results also revealed that the sample did not show psychological positive-negative reactions during and after the earthquake could effect on their emotional balance, there are no significant differences between male and female in the psychological positive reactions associated with earthquake compared to the negative reactions. articipant, the less of the psychological reactions and vice versa.